Exploring the Impact of the Merdeka Curriculum on Mathematics Education in Elementary Schools - Wibowo, Wahyu Ari; Suryatama, Handika; Siswanto, Deny Hadi (International Journal of Learning Reformation in Elementary Education, 2025)
This study aimed to analyze the implementation of the Merdeka Curriculum in mathematics learning at SDN Tegalsari (a state elementary school) during the 2024/2025 academic year using a qualitative descriptive method. The research focused on the planning, implementation, and evaluation of the curriculum, with subjects including the principal, vice principal for curriculum affairs, mathematics teachers, and students selected through purposive sampling. Data were collected through observations, interviews, and documentation, and analyzed using the interactive model of Miles & Huberman, which consisted of data reduction, data presentation, and conclusion drawing. The results indicated that the planning phase involved socialization, teacher training, the development of teaching materials, and the provision of facilities and infrastructure. The implementation emphasized project-based learning to strengthen the Profile of Pancasila Students, using a problem-solving approach to enhance students’ critical and creative thinking skills. The evaluation was conducted through diagnostic, formative, and summative assessments to measure the effectiveness of learning. This study highlighted the importance of school support in implementing the curriculum, including continuous teacher training and the optimization of learning facilities. Regular evaluations allowed schools to make strategic improvements to better meet students' needs and enhance overall education quality.